(untitled) - Cochran, Phillip E. (Victoria, Australia, 2004)
For Veterinary Technology and Pre-veterinary medicine students, here is a comparative veterinary anatomy and physiology manual. This is the only manual to cover cat dissection, sheep heart, brain and eye, and the pigÆs kidney. An introduction to laboratory equipment and techniques prepares the students for lab work. The book covers the muscular, digestive, respiratory, cardiovascular, urinary, reproductive, endocrine and nervous systems. It also covers skeletal anatomy of many species. Each chapter includes a physiology experiment to help illustrate some of the principles of physiology covered in lecture portions of the course instruction. Histology of tissues is also covered in this manual. To get the most out of this text, you should have a basic knowledge of biology.
Keywords: Veterinary anatomy,Veterinary physiology; Laboratory manuals,Laboratory manuals